ChemInform Abstract: Modular Access to Tetrasubstituted Imidazolium Salts Through Acid‐Catalyzed Addition of Isocyanides to Propargylamines. Issue 46 (November 2015) - Ghashghaei, Ouldouz; Reves, Marc; Kielland, Nicola; Lavilla, Rodolfo
Abstract The method is not suitable for aliphatic amines.